2014
DOI: 10.1007/s11033-014-3519-5
|View full text |Cite
|
Sign up to set email alerts
|

P53 related apoptosis in kidneys in CO2 pneumoperitoneum rat model: an immunohistochemical study

Abstract: Laparoscopic surgery techniques have been increasingly preferred to classic laparotomy by surgeons since 1987. However, this method may have some side effects on different intraabdominal organs including kidneys. The aim of this study is to evaluate the effects of different pressures of CO2 on p53 related apoptosis in kidneys. Totally 24 male rats were divided into four equal groups. CO2 is insufflated into rats' intraabdominal cavity in two different pressures of 10 and 20 mmHg during 1 h. However, in sham gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These effects may eventually cause hypoxic-ischemic damage, and when intraabdominal pressure is removed, ischemia/reperfusion injury may occur. This type of injury has been associated with oxidative damage and mitochondrial injuries (23), and apoptosis or death eventually occurs (24,25). As mentioned previously, certain patients undergoing surgery also present with a certain degree of kidney hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may eventually cause hypoxic-ischemic damage, and when intraabdominal pressure is removed, ischemia/reperfusion injury may occur. This type of injury has been associated with oxidative damage and mitochondrial injuries (23), and apoptosis or death eventually occurs (24,25). As mentioned previously, certain patients undergoing surgery also present with a certain degree of kidney hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, apoptosis increased in high CO 2 pressure. [ 24 ] In experimental studies, it was shown that high IAP directly increased renal[ 25 ] and hepatic[ 26 ] cell apoptosis. In our study, the high ovarian apoptotic scores during pneumoperitoneum were also demonstrated by histpathological study, as clearly shown in Figure 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, liver ischemia-reperfusion can increase the expression of Bax and cleaved caspase-3 [ 61 ]. Also a high CO 2 pneumoperitoneum pressures causes an increased apoptosis [ 62 ]. Bax and Bcl-2 are important genes in cell apoptosis progress.…”
Section: Discussionmentioning
confidence: 99%